2018
DOI: 10.1016/j.jmb.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Tight Turns of Outer Membrane Proteins: An Analysis of Sequence, Structure, and Hydrogen Bonding

Abstract: As a structural class, tight turns can control molecular recognition, enzymatic activity, and nucleation of folding. They have been extensively characterized in soluble proteins but have not been characterized in outer membrane proteins (OMPs), where they also support critical functions. We clustered the 4 to 6 residue tight turns of 110 OMPs to characterize the phi/psi angles, sequence, and hydrogen bonding of these structures. We find significant differences between reports of soluble protein tight turns and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…We compiled a data set of 138 OMBBs at <85% sequence similarity, 118 of which share <50% sequence similarity (Franklin et al, 2018a; Franklin and Slusky, 2018b). To determine evolutionary relationships, we selected homologues to the structurally solved proteins from a database of 279,715 nonredundant sequences and generated hidden Markov model (HMM) profile alignments.…”
Section: Resultsmentioning
confidence: 99%
“…We compiled a data set of 138 OMBBs at <85% sequence similarity, 118 of which share <50% sequence similarity (Franklin et al, 2018a; Franklin and Slusky, 2018b). To determine evolutionary relationships, we selected homologues to the structurally solved proteins from a database of 279,715 nonredundant sequences and generated hidden Markov model (HMM) profile alignments.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the C‐terminal BMB2 hydrophobic fragment confidently predicted as a helix may form kinks as a result of internal glycine residues (Fig. S7), as glycines are known to confer a high degree of local flexibility on polypeptides and are frequently found in protein regions where the polypeptide chain makes a sharp turn (Franklin & Slusky, 2018). It should be also noted that neither hydrophilic nor membrane‐embedded regions of BMB2 or TGB2 have a sequence similarity to reticulons, suggesting a reticulon‐independent evolutionary origin of viral proteins with reticulon‐like properties.…”
Section: Discussionmentioning
confidence: 99%
“…As the OMP approaches and moves through the membrane, it begins folding on a 'typical' liquid-disordered bilayer leaflet where phospholipids are free to diffuse before entering a region of low lateral mobility and increased hydration in the outer leaflet. These gradients of lateral mobility, lipid packing, hydration, and lipid headgroup polarity as an OMP inserts across the membrane normal could help to stabilize the tertiary structure of OMPs, particularly the hydrophilic loop regions (which can be >20 residues in length) ( 301 ), and drive the folding of the β-barrel domain to completion. Overall, therefore, the above studies have shown that the physical properties of the OM are highly complex and can vary dependent on the underlying lipid phase and the elastic stress, as well as the presence of OMPs and lipoproteins, and the LPR ( 175 , 214 , 302 ).…”
Section: More Than a MIX Of Lipid Typesmentioning
confidence: 99%